Characteristics Flakes From Rice Bran-Mocaf With Variation Of Beet Extract - Fitriyani, Reza; Widanti, Yannie Asrie; Mustofa, Akhmad (JITIPARI (Jurnal Ilmiah Teknologi dan Industri Pangan UNISRI), 2021)
Flakes were ordinary flat shaped cereal products used for breakfast. Flakes are made from various cereals like wheat, corn or cassava.Way to consuming flakes liquid milk added like cereal. In this study using mocaf flour and rice bran raw material with variations in the addition of beet fruit. The purpose of adding mocaf is to improve the taste and make the flakes blend more easily. The purpose of adding beets is to improve color and to increase antioxidant activity. The purpose of this study was to determine the optimal ratio of bran and mocaf and beets to obtain high fiber and antioxidant activity of flakes. This study uses a Completely Randomized Design (CRD) consisting of 2 factors. The first factor was the ratio of mocaf flour and rice bran (85:15, 90:10, 95:5) while the second factor was the addition of beet (10%, 20%, 30%).Â  The result showed that the best combination treatment that produced flakes with fiber and antioxidant activity was optimal and preferred by consumers is at 90:10 the ratio of mocaf flour and rice bran to the addition of beet extract 10%. In this tratments a 5,22% water content, 18.67% ash content, antionxidant activity 18,25%. Protein content 0,67%, fiber content 16,93% as well as test organoleptics which includes 2.97 color (pink almost violet), crispiness 2,89 (crispy), bran taste 2,67 (tasted), the taste of the mocaf 3,15 (tasted), and finally the overallpreference 2,87 (quiet liked).